Design of Sea Level Monitoring System Using Accelerometer with IoT Based - Juniarko Prananda; Agoes A. Masroeri; Vincentia Nindya Ayukinanthi (International Journal of Marine Engineering Innovation and Research, 2021)
Sea level is always changing, either influenced by meteorological aspects, gravitational forces, or geological effects. Monitoring the sea level is very beneficial, especially in such a big archipelago as Indonesia. This monitoring system is designed to use accelerometer sensor to sense the sea level changes vertically to obtain the level changes over time. This device is also featured by internet connection so that the data obtained from the sensor could be process on site using Arduino microcontroller and then sent to online website for remote monitoring process. This research is using experimental method, focusing on the electronic system design. The working flow of the research is started with literature studies and problem statement, then followed by system design, continued to software design, server building, and software and hardware integration. The last step is to test the device and analyze the result. After trial using simple pulley system, it is found that this device is able to sense the vertical level changes well, with an error for the sensor itself is at most 6 cm or about 2%. But there are some connection problems occurred between the device and the internet which resulted in a delay on the process, making the online monitoring system not perform as desired.